DETERMINANTS OF APARTMENT PRICES WITHIN HOUSING ESTATES OFNAIROBI METROPOLITAN AREA - Ndegwa, James N. (Machakos University, 2018)
The objective of this study is to establish the determinants that significantly influence apartment pricesthat are located within housing estates of Nairobi metropolitan area. Thedeterminants comprise of apartments features including: proximity to shopping malls, proximity to Nairobi’s central business district, proximity to schools, proximity to slums, presence of swimming pool, presence of balcony, size of the apartment, periodic rental income and land value. Both secondary and primary data sources were employed in the research and 30 housing estates where apartmentare located were selected for data collection purposes. Multiple regression analysis was employed for the secondary data and the findings indicated that:land value andsize of the apartmentshad a significant influence on apartment pricing. Descriptive statistical analysis findings indicated that proximity to shopping malls, proximity to Nairobi’s central business district, proximity to schools, presence of swimming pool, size of the apartments and land value had significant influence on apartment prices. Triangulation of secondary and primary data analysis results indicated a consistency rate of 50%. The recommendationof the study is that real estate stakeholders especially buyersshould focus onsize and land valueof apartments as these significantly influence apartment pricing in Nairobi metropolitan area. Key Words:Apartments, Determinants, Prices, Size and Land Value
Keywords: Apartments